Dragonfly Species Diversity in the Lemor Botanical Garden, East Lombok - Isnaini, Amalia; Jufri, A Wahab; Artayasa, I Putu (Jurnal Biologi Tropis, 2025)
Dragonflies are insect groups that play an essential role in ecosystem balance and are known as bioindicators of freshwater environmental quality. This study aimed to investigate and to calculate species diversity of dragonfly species in Lemor Botanical Garden, East Lombok. The research was conducted from October to December 2024 using an exploratory method with transect techniques and purposive random sampling at ten selected observation points representing different microhabitats. Species identification was carried out using odonata taxonomic references, and data were analyz ed using the Shannon-Wiener diversity index. The results showed there were 6 families and 21 species successfully identified. The diversity index of dragonfly species was 2.95, categorized as moderate, indicating that the area maintains relatively good environmental conditions that support various dragonfly species. These findings provide valuable baseline data for future biodiversity conservation and ecological studies in the region.